Disease Severity Indexes and Treatment Evaluation Criteria in Vitiligo - Tamihiro Kawakami; Takashi Hashimoto (Dermatology Research and Practice)
There is a current lack of consensus regarding methods of assessment of vitiligo. Recently, the Vitiligo Area Scoring Index (VASI) and the Vitiligo European Task Force (VETF) were proposed to offer more accurate measures of disease severity indexes and treatment evaluation criteria. It would make sense to combine the VASI with the VETF system. We proposed an original scale for treatment evaluation criteria in vitiligo based on VASI. We plan to add the digital image analysis system, health-related quality of life questionnaire, affected skin location, and skin color in the original scale.